2021
DOI: 10.3390/healthcare9111453
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Application for Quantitative Brain Fatigue Evaluation Based on Machine Learning and Ballistocardiogram

Abstract: Brain fatigue is often associated with inattention, mental retardation, prolonged reaction time, decreased work efficiency, increased error rate, and other problems. In addition to the accumulation of fatigue, brain fatigue has become one of the important factors that harm our mental health. Therefore, it is of great significance to explore the practical and accurate brain fatigue detection method, especially for quantitative brain fatigue evaluation. In this study, a biomedical signal of ballistocardiogram (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Left ventricular assist devices (LVAD) and mild traumatic brain injury are terms in Quadrant II. These terms refer to key areas of research where fiber optic sensing and machine learning have been used to solve critical healthcare problems [31,96,97]. For example, fiber-sensing technology has been used to improve LVAD monitoring and control.…”
Section: Analysis Of Emerging Wordsmentioning
confidence: 99%
“…Left ventricular assist devices (LVAD) and mild traumatic brain injury are terms in Quadrant II. These terms refer to key areas of research where fiber optic sensing and machine learning have been used to solve critical healthcare problems [31,96,97]. For example, fiber-sensing technology has been used to improve LVAD monitoring and control.…”
Section: Analysis Of Emerging Wordsmentioning
confidence: 99%
“…They performed a study on patients after vascular intervention surgery and healthy subjects to prove the ability of BCG in long-duration monitoring of high-risk patients. Moreover, Liu et al [ 167 ] and Xu et al [ 168 ] revealed that the HRV parameters obtained from BCG could be used as the identifying indicators to detect hypertension and brain fatigue, respectively.…”
Section: Studies That Combine Cardiac and Pulmonary Informationmentioning
confidence: 99%
“…Advanced features such as wireless transmission, miniaturized amplifiers ( Wascher et al, 2023 ), and dry electrodes ( Ramírez-Moreno et al, 2021 ) have enhanced the application of highly portable EEG head-mounted devices, proving crucial for research in real mobile environments. Technologies like the ballistocardiogram (BCG), using a fiber sensor cushion ( Xu et al, 2021 ) or photoplethysmogram (PPG) integrated into a helmet ( Wilson et al, 2020 ) have enabled the simultaneous collection of biological signals alongside the primary task, offering the capability to capture changes in the operators’ functional status before an alteration in task performance occurs. With superior temporal resolution compared to subjective methods, these approaches serve as pivotal tools for real-time mental workload assessment during tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated a correlation between ECG signals and psychomotor vigilance task (PVT) performance, as well as the effectiveness of HRV indices in assessing cognitive task-related errors. Leveraging sensitive features extracted from ECG, algorithms like learning vector quantization and random forest tree classifiers achieve impressive accuracy in identifying fatigue states, underscoring HRV as a potential indicator for evaluating worker fatigue ( Chua et al, 2012 ; Zhao et al, 2012 ; Pan et al, 2021 ; Xu et al, 2021 ; Takada et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%